Some initial results of 50 MHz meteor radar observation at Syowa Station - Ogawa, Tadahiko; Igarashi, Kiyoshi; Kuratani, Yasukazu; Fujii, Ryoichi; Hirasawa, Takeo (1985)
P(論文) A 50MHz doppler radar installed at Syowa Station, Antarctica, in 1982 acts as a meteor radar, when an operator assigns a meteor mode operation to the radar. This paper describes some initial results obtained from the meteor echo data covering the period 29 December 1982-15 January 1983. The altitude distribution and hourly occurrence probability of echoes and also the mean zonal and meridional wind components derived from doppler velocities of meteor trails are nearly consistent with the results obtained at mid- and high-latitudes in the opposite hemisphere. Evidence showing that neutral winds may be partly modified by electric fields, Joule heating or Lorentz force appearing under geomagnetically disturbed condition is also presented. departmental bulletin paper